STUDY OF PHYSICAL PROPERTIES OF TAPER STRUCTURED FIBER OPTIC SENSORS - Frazna Parastuti; Dyah Hikmawati; Herri Trilaksana (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
Along with its development, optical fiber has been modified into sensors because of its various advantages. In the fabrication of a modified fiber optic sensor in the form of a taper innovation, the sensor geometry becomes the main parameter that can affect the sensitivity of the sensor. The fiber taper works by allowing the evanescent waves out of the waveguide to interact with the stimulus, thus providing a sensor mechanism. The fabrication of the fiber taper in this study was carried out using the drawing and heating method continuously and simultaneously. Based on this fabrication process, the optical fiber is pulled using an autograph until it enters the plastic deformation region. Mechanical properties analysis showed that the optical fiber has a stress of 54.21 MPa and an elastic modulus of 2.46 GPa. It was also found that the optical fiber experienced an elongation of up to 11.02%. The results of the digital microscope test showed that the taper process succeeded in reducing the diameter of the optical fiber by 18.40%. Besides the ease of processing, the advantage of fabrication using this method is that the mechanical properties are measured in real-time, making this method reproducible on a mass scale.